(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
Adjectives are an essential part of speech that help to describe or modify nouns or pronouns. They provide additional information about the noun or pronoun, such as its size, color, shape, or opinion. Adjectives play a crucial role in making our language more vivid and expressive. In this article, we will explore the different types of adjectives and their functions.